7 - From the Hub of Lagos: Horizontal Integration for the Southwest Region of Nigeria, a Developmental Imperative - Kenneth Chukwuemeka Nwoko; Omon Merry Osiki (Afrika Zamani, 2022)
In Nigeria, the experiment at federalism has demonstrated that no meaningful development could be achieved with the present structure of economically and politically weak federating units and a dominating strong centre. The imperative for economic development, therefore, calls for the strengthening of the federating state units. This article investigates the nexus between horizontal integration of the southwest states of Nigeria into a regional bloc within the Nigerian state and the socio-economic development of the region, in relation to the long-term economic development plan of Nigeria. It argues that this horizontal integration is the major catalyst necessary for the attainment of the vision 20:2020 goal of the country. The success of this integration in the southwest would serve as a model for the other regions of the country. This study is an attempt to encourage regional integration and from it regional planning as a critical element of the new economic development strategies of the federating state units in Nigeria in order to provide the spatial development framework for other strategies to succeed.